Penguatan Daya Saing UMKM Desa Sialaman melalui Program Edukasi Produksi Tempe Dokumentasi Kegiatan KKN Kecamatan Sipirok - Pajhar Ainnun Berutu; Rahman Saleh Nasution; Tukma Putri Romaito Tanjung; Yogi Pandapotan Siregar; Salahuddin Harahap (Jurnal Pengabdian Masyarakat Waradin, 2026)
Community engagement activities through the KKN program in Sialaman Village, Sipirok Subdistrict, South Tapanuli Regency were designed to strengthen the capabilities of local MSME actors in tempeh production. Program implementation used participatory methods that actively involved the community, including initial observation, counseling, and production practice stages. A total of 30 people participated, including PKK mothers, village youth, and small-scale local entrepreneurs. The learning by doing approach proved its effectiveness in transferring technical skills to participants. Observations during the activity showed that 90% of participants demonstrated high enthusiasm and gained new insights regarding the transformation of soybeans into economic commodities. This program successfully awakened entrepreneurial spirit and opened business opportunities based on sustainable local agricultural products.